Isolation and identification of antibacterial and antispore compounds from Syzygium polyanthum L. leaves - Mohamed Abobaker, Abdelgani (2018)
In this study, the antibacterial and antispore activities in Syzygium polyanthum L. leaves extract were evaluated against vegetative cells and spores of Bacillus cereus ATCC33019, B. megaterium ATCC14581, B. pumilus ATCC14884 and B. subtilis ATCC6633. The susceptibility test showed that all tested vegetative cells of Bacillus were inhibited by S. polyanthum extract, with the range of inhibition zone between 10.00 to 16.00 mm. The extract could inhibit the growth of Bacillus with MIC ranged 0.02 to 0.08 mg/mL. These bacteria can be completely killed at different MBC valueup to 0.63 mg/mL. Time-kill curve study showed that. Bacillus sp. can be killed by S. polyanthum L. extract at 8× for 1 h. Moreover, S. polyanthum L extract deactivated more than 3-Log of Bacillus sp. spores at a concentration of 1.0% after 1 hour of incubation. The antibacterial and sporicidal activity of S. polyanthum L. extract was stable at different temperatures and pHs treatment. Scanning electron microscope showed that structure of the spores was destroyed after treated with 1.0% S. polyanthum L. extract for 1 hour. 1H NMR analyses showed that the young leaves extracts were found to be richer in sugars, and glycosides, whereas the old leaves contained higher levels of fatty acid components. LCMS analysis identified the presence of active compounds in S. polyanthum L. extract which included gallic acid, quinic acid, and oleanolic acid. The β-sitosterol and oleanolic acid were successfully isolated from the methanol extract of S. polyanthum L. β-sitosterol was able to inhibit the growth of all tested Bacillus sp. with the range of inhibition zone between 11.7 and 12.3 mm. The growth of all tested Bacillus sp. can be inhibited by MIC value of 7.81 μg/ml and can be killed with MBC value of 15.62 μg/ml. Meanwhile, oleanolic acid was able to inhibit the growth og all tested Bacillus sp. with the range of inhibition zone between 12.2 and 13.5 mm. MIC and MBC values of oleanolic acid on all tested Bacillus sp. was 31.25 and 500 μg/ml, respectively. Finally, β- sitosterol and oleanolic acid at concentration of 1.00 μg/mL (0.1%) can killed 100% of all tested Bacillus sp. spores. In conclusion, S. polyanthum extract and its compounds exhibited antimicrobial and sporicidal activity against Bacillus species, thus it can be developed as anti-Bacillus agent.